A Metaheuristic Approach for Propagation-Model Tuning in LTE Networks (Informatica, 2014)
When deploying a new mobile technology such as LTE, it is crucial to identify the factors that affect theradio network in terms of capacity and quality of service. In this context, network coverage is arguablythe single most influential factor. This work presents a metaheuristic-optimization approach that automaticallyadapts the parameters of a signal-propagation model. The optimization procedure is performed percell, enabling the calculation of accurate network-coverage predictions. The evaluation of the proposedapproach is carried out on two different regions in Slovenia, where Telekom Slovenije, d.d., provides LTEcoverage. The results show radio-propagation predictions of improved quality when compared to manualand analytical methods.